Baricitinib-induced blockade of interferon gamma receptor and interleukin-6 receptor for the prevention and treatment of graft-versus-host disease. Issue 11 (November 2018) - Choi, Jaebok; Cooper, Matthew; Staser, Karl; Ashami, Kidist; Vij, Kiran; Wang, Bing; Marsala, Lynne; Niswonger, Jessica; Ritchey, Julie; Alahmari, Bader; Achilefu, Samuel; Tsunoda, Ikuo; et al.
Abstract The therapeutic benefits of allogeneic hematopoietic stem cell transplantation (allo-HSCT) are derived from the graft-versus-leukemia (GvL) effects of the procedure. There is a strong association between the GvL effects and graft-versus-host disease (GvHD), a major life-threatening complication of allo-HSCT. The limiting of GvHD while maintaining the GvL effect remains the goal of allo-HSCT. Therefore, identifying optimal therapeutic targets to selectively suppress GvHD while maintaining the GvL effects represents a significant unmet medical need. We demonstrate that the dual inhibition of interferon gamma receptor (IFNγR) and interleukin-6 receptor (IL6R) results in near-complete elimination of GvHD in a fully major histocompatibility complex–mismatched allo-HSCT model. Furthermore, baricitinib (an inhibitor of Janus kinases 1 and 2 (JAK1/JAK2) downstream of IFNγR/IL6R) completely prevented GvHD; expanded regulatory T cells by preserving JAK3-STAT5 signaling; downregulated CXCR3 and helper T cells 1 and 2 while preserving allogeneic antigen-presenting cell-stimulated T-cell proliferation; and suppressed the expression of major histocompatibility complex II (I-Ad), CD80/86, and PD-L1 on host antigen-presenting cells. Baricitinib also reversed established GvHD with 100% survival, thus demonstrating both preventive and therapeutic roles for this compound. Remarkably, baricitinib enhanced the GvL effects, possibly by downregulating tumor PD-L1 expression.